Nutraceutical potential, phytochemistry of hemp seed (Cannabis sativa L.) and its application in food and feed: A review - Madhu Kamle; Dipendra Kumar Mahato; Bharti Sharma; Akansha Gupta; Ajay Kumar Shah; M M Chayan Mahmud; Swati Agrawal; Jyoti Singh; Prasad Rasane; Amritesh Chandra Shukla; Pradeep Kumar (Food Chemistry Advances, 2024)
Hemp seeds are gaining increasing attention in the realm of research due to their multifaceted nutritional and pharmaceutical properties. Notably, these seeds offer a rich source of protein, carbohydrates, polyunsaturated fatty acids, vitamins, and minerals, making them a valuable addition to one's diet therefore, growing interest among researchers globally. A comprehensive literature review was conducted on the prominent databases Scopus, Elsevier, and PubMed using the keywords ''Hempseed,'' ''Phytochemistry,'' ''Nutraceuticals,'' and their food and feed applications. Studies suggest that these compounds exhibit therapeutic potential against conditions such as epilepsy, certain neurological disorders (Parkinson's and Alzheimer's diseases), and cardiovascular issues. Additionally, hemp seeds possess other notable properties, such as anti-cancer, anti-inflammatory, and immunomodulatory effects. They are also used as a dietary supplement to alleviate headaches, insomnia, high cholesterol levels, and premenstrual syndrome symptoms in women. Hempseed oil, powder, and flour are utilized to enhance the phenolic activity and antioxidant properties of food products. Additionally, hempseed cake, generated after cold pressing, boasts a high protein concentration, making it a valuable feed for ruminants. However, further research and clinical trials are necessary to fully understand and harness the potential of hemp seeds for functional foods and nutraceutical applications.